If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8h + -11(h + 4) = -77 Reorder the terms: 8h + -11(4 + h) = -77 8h + (4 * -11 + h * -11) = -77 8h + (-44 + -11h) = -77 Reorder the terms: -44 + 8h + -11h = -77 Combine like terms: 8h + -11h = -3h -44 + -3h = -77 Solving -44 + -3h = -77 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + -3h = -77 + 44 Combine like terms: -44 + 44 = 0 0 + -3h = -77 + 44 -3h = -77 + 44 Combine like terms: -77 + 44 = -33 -3h = -33 Divide each side by '-3'. h = 11 Simplifying h = 11
| 7x+4x=-x | | 1108473/4=x | | 7(z+11)=4(z+11) | | 3X^2-20x+15=0 | | -15+16+19d=20+19d | | 12(2x-9)=4(6x+6) | | 6x-17=4x+31 | | (-87)+x=-25 | | 0=8v-8v | | 2(3k+7)+12(2+k)=-16 | | -3x+6x=-12+4x-5x | | 0.06/18 | | -16q+7=-16q-2 | | 38+x=82 | | 11a=24+8a | | -2-4-3b=-6-10b | | 7x+6=7(x-7) | | -10c-10=2-8c | | -5n-8=1-8n | | 9f=10+9f | | 6n-8(n+5)=-70 | | -4-8n+8n=n+3 | | -7m+m-4=-6m+5 | | 6(x+1)/5=5x-5 | | 7x+5=2x+1 | | -x+41+8x-9=-3 | | 0.40x+0.45(20)=0.20(35) | | -10t=-10t+9 | | 4(3y-2)/7=3y-5 | | 7(x-4)=4x-16 | | 1.6x=.8x | | 2/7x+3/7=-1/7 |